Legal Status of Diplomats: Duties, Restrictions, Prohibitions - T. A. Zanko (Vestnik MGIMO-Universiteta)
This article provides analysis of such elements of the legal status of diplomats as obligations, prohibitions, restrictions and responsibility. Elements of the legal status are evaluated through the lens of comparative research and include the experience of diplomatic service legal regulation in the former Soviet Union countries as well as in other foreign countries.